Surface roughness of composite resins submitted to three different finish and polish systems (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the in vitro performance of three different finishing and polishing systems, concerning providing better surface smoothness. Materials and methods: 2x4 mm specimens were made with 6 composites: Filtek Z250, Classic Herculite, Opalis, Filtek Z350, Zirconfilll and Estelite Omega, which were subsequently divided into four groups according to a different finishing system (Sof-Lex, OptiDisc, Praxis and Control). After polishing, twelve specimens were distributed to each of the six resins studied, making a total of 72 samples (n = 3), which had their roughness evaluated by a contact roughnessmeter. The Kruskal-Wallis test and Dunn's post-test with Bonferroni adjustment were used to search for significant differences. Values ​​were considered significant when p